The China alternative: Changing regional order in the Pacific Islands - Graeme Smith; Terence Wesley-Smith (ANU Press, 2021)
In this collection, 17 leading scholars based in Solomon Islands, Fiji, Papua New Guinea, Timor-Leste, Australia, New Zealand, the United States and China analyse key dimensions of the changing relationship between China and the Pacific Islands and explore the strategic, economic and diplomatic implications for regional actors. The China Alternative includes chapters on growing great power competition in the region, as well as the response to China's rise by the US and its Western allies and the island countries themselves. Other chapters examine key dimensions of China's Pacific engagement, including Beijing's programs of aid and diplomacy, as well as the massive investments of the Belt and Road Initiative. The impact of China's rivalry for recognition with Taiwan is examined, and several chapters analyse Chinese communities in the Pacific, and their relationships with local societies. The China Alternative provides ample material for informed judgements about the ability of island leaders to maintain their agency in the changing regional order, as well as other issues of significance to the peoples of the region.
Keywords: 330; China; Pacific Islands; Taiwan; cold war; Internationale Beziehungen; Internationale Wirtschaftsbeziehungen; China; Asiatisch-pazifischer Raum; Ozeanien